PENGEMBANGAN MODUL AJAR DIGITAL PADA MATA KULIAH MEDIA DAN SUMBER BELAJAR PAUD - Setianingsih, Hesti (Information Technology Education Department, 2026)
The purpose of this study is to develop digital module-based teaching materials for the Early Childhood Education Media and Learning Resources course. This study uses content expert and media expert assessments to determine the feasibility of the module. This research process was conducted using the Research and Development (R&D) method with the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. One of the research subjects is 100 students from the Early Childhood Education Study Program at Tadulako University who are in their second semester. This research tool uses validation sheets from subject matter experts and media experts, and the data collection methods are interviews and questionnaires. Quantitative and qualitative analyzes were performed on the data. The research results show that the developed digital module has an average feasibility percentage of 82.96%, indicating that it is suitable for use as lecture material. This research is limited to trial subjects involving only second-semester students and limited expert validation tools. This research produced alternative teaching materials that are interactive and flexible, available to both lecturers and students. Socially, this research supports the transformation of digital learning in higher education and the improvement of digital literacy among prospective early childhood education teachers. The novelty of this research lies in the development of a digital module tailored to the ADDIE model, specifically designed for the Early Childhood Education Media and Learning Resources course at Tadulako University. Keywords: Digital Module; Media; Learning Resources.